Phenomena of optical metamaterials - Gric, Tatjana; Hess, Ortwin, 1966- (Micro & nano technologies., 2019)
Phenomena of Optical Metamaterials provides an overview of phenomena enabled by artificial and designed metamaterials and their application for photonic devices. The book explores the study of active metamaterials with tunable and switchable properties and novel functionalities, such as the control of spontaneous emission and enhancement. Topics addressed cover theory, modelling and design, applications in practical devices, fabrication, characterization, and measurement, thus helping readers understand and develop new artificial, functional materials.